2022
DOI: 10.3389/fnmol.2022.873658
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane-Induced Apoptosis in the Mouse Cerebral Cortex Follows Similar Characteristics of Physiological Apoptosis

Abstract: General anesthetics are capable of inducing neuronal apoptosis during the rapid synaptogenesis of immature mammalian brains. In this vulnerable time window, physiological apoptosis also occurs to eliminate excess and inappropriately integrated neurons. We previously showed that physiological and ketamine-induced apoptosis in mouse primary somatosensory cortex (S1) followed similar developmental patterns. However, since sevoflurane is more widely used in pediatric anesthesia, and targets mainly on different rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Mechanism studies indicated that neonates could exhibit brain structural abnormalities following prolonged exposure to 2.5–4% sevoflurane [ 34 ]. Inhaled anesthetics related neurotoxicity included neurogenesis alteration, increased apoptosis and reduced proliferation of neural stem cells [ 35 , 36 ]. Therefore, non-injurious anesthetics and anesthesia strategy need more research.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism studies indicated that neonates could exhibit brain structural abnormalities following prolonged exposure to 2.5–4% sevoflurane [ 34 ]. Inhaled anesthetics related neurotoxicity included neurogenesis alteration, increased apoptosis and reduced proliferation of neural stem cells [ 35 , 36 ]. Therefore, non-injurious anesthetics and anesthesia strategy need more research.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, Gadd45a was found induce Gadd45a-dependant apoptosis in response to NF-kappa B signaling ( 37 ) and serves as important links between NF-kappa B and MAPK signaling ( 38 ). Sevoflurane was found to impair the AMPK/FoxO3a signaling pathway activation leading to apoptosis of mouse hippocampal neurons ( 39 ) and in mouse cerebral cortex ( 40 ). FoxO signaling is implicated in increased M1 type polarization of macrophages in Sevoflurane related postoperative cognitive dysfunction ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akt can deregulate cell survival through pro-apoptotic signals that directly interfere with the production of transcription factors, such as Forkhead box O (FoxOs). Studies have shown that the Akt/FoxO1 signaling pathway mediates sevoflurane-induced neuronal apoptosis in neonatal mice ( 6 ), thereby, activating this pathway can inhibit apoptosis of neuronal cells in neonatal brains ( 7 , 8 ). In addition, activation of the PI3K/Akt/mTOR signaling pathway can improve general anesthetic-induced neuroinflammation in rats and reduce the neurotoxic effect of general anesthetics ( 9 , 10 ).…”
Section: Related Signaling Pathwaysmentioning
confidence: 99%